Impact of Prescribers’ Adherence to Clinical Practice Guidelines for Hypertension on Hypertension Control - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study evaluates physicians’ adherence to Malaysian Clinical Practice Guidelines for Hypertension 2013 (MCPGs-HPT-2013) and the factors influencing patients’ adherence to antihypertensive medications. Materials and Methods: Among a cohort of randomly selected 170 hypertensive patients, the prescribing trends of physicians were compared with MCPGs-HPT 2013. Univariate and multivariate analyses (odds ratio [OR], 95% CI) were done to investigate the physician’s adherence to MCPGs-HPT-2013. Results: Patients that had three concurrent clinical conditions and prescribed with angiotensin-converting enzyme inhibitors (P < 0.05, OR = 2.989) were affected the most with physicians’ non-adherence with MCPGs-HPT-2013. Conclusion: Surprisingly, <50% of the total patients received guidelines compliant pharmacotherapy that emphasizes the need for strict adherence to MCPGs-HPT-2013 in Malaysia.